BOARD CHARACTERISTICS AND THE LIKELIHOOD OF FINANCIAL STATEMENT FRAUD - Subair, Muhammed Lawal; Salman, Ramat Titlayo; Abolarin, Ayodeji Fatai; Abdullahi, Abdulrasheed Taiwo; Othman, Akeem Sisofa (Copernican Journal of Finance & Accounting, 2020)
The study examines the effect of board characteristics on financial statement fraud likelihood of quoted manufacturing firms in Nigeria. The scope of the study covers board attributes such as board independence, board expertise and board diligence; and the beneish M-score was used as the measure of fraud likelihood. This study utilized a quantitative research design. The sample covered 39 manufacturing companies in the Nigerian Stock Exchange (NSE) as at 2019. Secondary data was utilized for this study and the data were extracted from the annual reports of corporate organizations for the period 2013-2019 financial years. The binary logit regression was employed as the method of data analysis in the study. The findings reveal that the odd ratio of board independence, board expertise and board diligence negatively and significantly reduce the log odds of financial statement fraud in manufacturing firms in Nigeria. The study concludes that there is a need for boards to be more effective in their monitoring roles to reduce the occurrence of fraud.